Sustainability and business schools in Singapore: an empirical study on student attitudes - Lau, Hailey (2024)
Sustainability has become an urgent global challenge, and higher education is not spared. Higher education has been called to step up and contribute towards the United Nations Sustainable Development Goals (SDG). Much research has been done in the areas of sustainability development and responsible management education, but global progress towards the achievement of the SDGs has been slow. Coupled with the aftermath of the COVID-19 pandemic, higher education has transformed in many ways, impacting recruitment efforts and the student experience after the pandemic, especially from a sustainability perspective. This paper aims to examine business schools in Singapore by exploring student consideration factors when selecting a programme choice of study, differences in the student experience during and after the pandemic, and what is important to the student experience especially from the sustainability perspective. The study uses a descriptive mixed methods methodology where both quantitative and qualitative approaches of data collection, analysis and integration of findings were done in one study. An online survey questionnaire was distributed to 139 participants, where data was collected from the quantitative multiple-choice, ranking and Linkert scale questions, and qualitative open-ended questions. The data would be analysed according to the natural clusters of gender and country of origin. From the results, there was no major difference in attitudes between genders and local and international students. However, all students are concerned and expect the school to provide support on mental well-being. The analysis also revealed that sustainability perceptions and awareness are low, and that students received very little education on sustainability. Despite much research on sustainability development and responsible management education, there is a lack of translation of theory into practice, hence a big gap between theory and practice still exists. To close the gap, much needs to be done in order to move towards the United Nations SDG by 2030.